2002
DOI: 10.1088/0953-2048/15/6/324
|View full text |Cite
|
Sign up to set email alerts
|

(Cu,Tl)Ba2Ca3Cu4Ox compositions: II. Heating rate applied to synthesis of superconducting ceramics

Abstract: Superconducting samples with a starting composition Cu0.5TlxBa2Ca3Cu4O12 (x = 1–0.35) were prepared in Au tubes from oxides by using different heating rates. The optimum heating rate was 0.11 °C min−1 applied between 860 and 880 °C. These samples show the highest content of 1234 phase and the lowest of Ba–Cu–O phases as well as the highest critical temperatures. The highest values were Tc = 119.2 K and Tc0 = 115.1 K. All samples show Jc values around 6 × 105 A cm−2, at 60 K and 0.5 T. In the rest of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Very small amounts of impurities such as (Cu, Tl)-1223 and Ba 2 Cu 3 O 6 appear in the diffraction patterns. These impurities were also observed by Badica et al [4] in (Cu, Tl)-1234 phase, prepared using solid-state reaction technique. The volume fractions of these phases can be estimated using various methods [11,12].…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…Very small amounts of impurities such as (Cu, Tl)-1223 and Ba 2 Cu 3 O 6 appear in the diffraction patterns. These impurities were also observed by Badica et al [4] in (Cu, Tl)-1234 phase, prepared using solid-state reaction technique. The volume fractions of these phases can be estimated using various methods [11,12].…”
Section: Resultssupporting
confidence: 71%
“…3(a-d), respectively. More grains with regular plate-like or bar-like can be observed in x = 0.0, 0.2 wt.% and 0.6 wt.%, indicating the formation of (Cu, Tl)-1234 phase [4]. Some blocks of several composed plates or bars were also observed, especially in x = 0.6.…”
Section: ×100mentioning
confidence: 89%
See 2 more Smart Citations
“…It is clear that the samples morphology consists of randomly oriented plate-like grains, indicating the phase formation of (Cu 0.5 Tl 0.5 )-1223. Badica et al [37] found that grains with plate-like morphology was an advanced stage of (Cu Tl)-Ba 2 Ca 3 Cu 4 O z phase. Also, it is clear for all the samples that there is a little number of irregular shaped and spherical grains embedded between the plate-like grains of (Cu 0.5 Tl 0.5 )-1223 phase.…”
Section: Resultsmentioning
confidence: 99%